Russia under the old regime - Pipes, Richard (Penguin Books, 1995)
Newly revised for this edition, Richard Pipes's highly acclaimed study analyses the evolution of the Russian state from the ninth century to the 1880s and its unique role in managing Russian society. The harsh geographical conditions and sheer size of the country prevented the creation of participatory government, and a 'patrimonial' state emerged in which Russia was transformed into a gigantic royal domain. Richard Pipes traces these developments and goes on to analyse the political behaviour of the principal social groupings - peasantry, nobility, middle-class and clergy - and their failure to stand up to the increasing absolutism of the tsar. In order to strengthen his powers legal and institutional bases were set up that led to the creation of a bureaucratic police state under the Communists.